Manajemen pengelolaan pembelajaran berbasis TIK - Mohamad Miftah (ARKA INSTITUTE, 2022)
The contribution of ICT to the world of learning is considered very beneficial. Moreover, integrating ICT into teaching and learning practices. The use of ICT in education is suitable for managing more student-centered learning. This can create a more passionate learning activity. However, institutions are still lacking in providing proper ICT training for instructors to develop their technical ICT skills. The article was written with the aim of analyzing the literature review from various sources, both books and research results. The results showed that the participants, both instructors and students, had a positive attitude towards ICT and sufficient knowledge and positive understanding of ICT and its potential in teaching and learning. However, there are no examples of the model, the instructor provides opportunities for students to use ICT in a meaningful context. It is hoped that this article will be useful for teachers and school administrators on how to manage ICT-based learning, so that learning outcomes are maximized.